1985
DOI: 10.1159/000124193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lesions of the Corticomedial Amygdala on the Nocturnal Prolactin Surge

Abstract: It has been reported that the corticomedial amygdala (CMA) is involved in regulating various hypothalamic and neuroendocrine events. This study examined the role of the CMA in the regulation of the nocturnal surge of prolactin (PRL) induced by cervical stimulation (CS). Female Sprague-Dawley rats were ovariectomized, received CMA or sham lesions, and were placed on a reversed lighting schedule of 14 h light: 10 h dark. 3 weeks later, all rats were cervically stimulated. 5 days after CS (CS + 5) rats were fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Necrotic responses to excitatory amino acid injections are well described, comprising an early phase lasting 1-14 d after infusion and a later stage that is characterized by an infiltration of astrocytic glia cells Marty et al, 1991). In the present experiment, glial coverage was observed in brains taken 16 d after NMDA infusion, and nocturnal PRL surges observed 6 -7 d after NMDA infusion were diminished in magnitude, as is characteristic for MEA-lesioned females (Clark and Gala, 1985;Polston and Erskine, 2001). Nevertheless, several lines of evidence suggest that it is the initial excitatory effect of NMDA on MEA neurons that is responsible for the present effects.…”
Section: Discussionsupporting
confidence: 58%
“…Necrotic responses to excitatory amino acid injections are well described, comprising an early phase lasting 1-14 d after infusion and a later stage that is characterized by an infiltration of astrocytic glia cells Marty et al, 1991). In the present experiment, glial coverage was observed in brains taken 16 d after NMDA infusion, and nocturnal PRL surges observed 6 -7 d after NMDA infusion were diminished in magnitude, as is characteristic for MEA-lesioned females (Clark and Gala, 1985;Polston and Erskine, 2001). Nevertheless, several lines of evidence suggest that it is the initial excitatory effect of NMDA on MEA neurons that is responsible for the present effects.…”
Section: Discussionsupporting
confidence: 58%
“…Prolactin release in P/PSP rats was also influenced by MePD integrity, as prolactin secretion was blunted across all times of day 6–7 days postmating in MePD‐lesioned females. A specific inhibition of the nocturnal prolactin surge after radiofrequency lesion of the corticomedial amygdala has been reported to occur 12 and 15 but not 8 days after VCS (30). In the present experiment, the suppression of prolactin secretion in BI females was marginally significant compared to sham females (P ≤ 0.06); however, when compared to IC females which showed slightly higher prolactin than did sham rats, the suppression of prolactin release in BI females was statistically significant (P ≤ 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the VMH seems to have a uniformly stimulatory control over both nocturnal and diurnal surges [21, 22, 35]. The amygdala has been shown to alter the incidence of induction of pseudopregnancy [36, 37]and the termination of the nocturnal surge [38]. In addition, our previous work showed that Fos expression in the mPOA and VMH exhibited activated neuronal activity during the mating-induced nocturnal and diurnal PRL surges [23].…”
Section: Discussionmentioning
confidence: 99%
“…By using a double-label immunofluorescent technique, Tetel et al [30]found that high percentages of VCS-induced Fos-positive neurons in the mPOA, mAMYG and VMH also contained estrogen receptor-immunoreactivity. Given that these brain areas are important in the regulation of both hormone-induced afternoon PRL surge [12, 13]and VCS-induced twice daily PRL surges [21, 22, 34, 35, 38], the subset of neurons responding to estrogen and VCS may integrate the two forms of stimuli and directly or indirectly contribute to the PRL surge. However, the magnitude of the increase in Fos expression in these brain areas was considerably more subtle during the proestrous PRL surge than following mating.…”
Section: Discussionmentioning
confidence: 99%